2023
DOI: 10.1007/s13399-023-03745-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical applications of lignin-derived chemicals and lignin-based materials: linking lignin source and processing with clinical indication

Abstract: Lignocellulosic biomass is one of the most abundant bioresources on Earth. Over recent decades, various valorisation techniques have been developed to produce value-added products from the cellulosic and hemicellulosic fractions of this biomass. Lignin is the third major component accounting for 10–30% (w/w). However, it currently remains a largely unused fraction due to its recalcitrance and complex structure. The increase in the global demand for lignocellulosic biomass, for energy and chemical production, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 234 publications
0
12
0
Order By: Relevance
“…Then, the pressure is released rapidly and the steam present in the biomass expands, causing fibers to break down. 13 This process is considered to be one of the most efficient and cost-effective, although it is important to note that it is often used as pretreatment of lignocellulosic biomass before other processes are applied, 26 and there is a large heterogeneity of the lignin obtained. 13 Hydrolysis lignin, on the other hand, is usually a by-product of bio-ethanol production from cellulose hydrolysis.…”
Section: Towards Sustainable Delignification Methods Of Lcbmentioning
confidence: 99%
“…Then, the pressure is released rapidly and the steam present in the biomass expands, causing fibers to break down. 13 This process is considered to be one of the most efficient and cost-effective, although it is important to note that it is often used as pretreatment of lignocellulosic biomass before other processes are applied, 26 and there is a large heterogeneity of the lignin obtained. 13 Hydrolysis lignin, on the other hand, is usually a by-product of bio-ethanol production from cellulose hydrolysis.…”
Section: Towards Sustainable Delignification Methods Of Lcbmentioning
confidence: 99%
“…Lignin is an aromatic polymer with abundant phenolic and aliphatic hydroxyl groups, and it has many chemically reactive sites (such as the C3 and C5 positions of the aromatic ring of lignin), which enable it to form multifunctional hydrogels [4,51]. Typically, all types of lignin have been utilized to fabricate lignin-based hydrogels [51][52][53][54]. In general, lignin has been combined with other polymers via crosslinking copolymerization, crosslinking monomers with grafted lignin, or interpenetrating lignin into a polymer network to produce lignin-based hydrogels.…”
Section: Hydrogel-based Lignin Carriersmentioning
confidence: 99%
“…In general, lignin has been combined with other polymers via crosslinking copolymerization, crosslinking monomers with grafted lignin, or interpenetrating lignin into a polymer network to produce lignin-based hydrogels. It has also been demonstrated that lignin can be copolymerized with crosslinking agents to directly prepare lignin-based hydrogels [53][54][55]. Recently, Evstigneev [56] also disclosed a patent describing a method to produce a pure lignin hydrogel without adding any copolymer.…”
Section: Hydrogel-based Lignin Carriersmentioning
confidence: 99%
“…Lignin, due to its properties, has a wide range of applications, ranging from precursor of several high added-value chemical products, to its use in the production of bio-materials or even biofuels [ 23 , 24 ]. Hemicelluloses, among other possible applications, can be used to obtain different oligosaccharides with diverse applications [ 25 ].…”
Section: Introductionmentioning
confidence: 99%